PERANAN LEMBAGA PEMBIAYAAN EKSPOR TERHADAP USAHA KECIL DAN MENENGAH BERDASARKAN UU NO. 2 TAHUN 2009 TENTANG LEMBAGA PEMBIAYAAN EKSPOR INDONESIA - M. Tino Sendy Pangestu (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACTIONIndonesia's economy is increasingly integrated into the global economy that puts the value of competitiveness, product quality and efficiency increasingly emphasized the need for the application of the principle of economic democracy in a legislation. The development of a sustainable economy should be able to increase the value added at each link of the national economy so that the Indonesian people are able to realize the economic sovereignty of Indonesia which is one of the benchmark is the increased capability in producing goods and services that are competitive in the global market. Achievement of this goal is becoming increasingly relevant for foreign trade, contributing in the national economy is increasingly important. Problems in export activity would arise when SMEs export oriented itself does not seek to minimize the obstacles to its activities as a result of lack of understanding of the procedures of export activity.      Therefore we need an independent export financing institutions that are capable of supporting a low-cost export financing to small and medium enterprises, export financing institutions like the developed world that have special advantages that have access to low cost international funding. Thus, the agency can provide export credits with low interest, so that the government does not have to provide interest subsidies or special policies to support export activities. Look at the experience of other countries, in order to optimize the foreign trade transactions, the Indonesian Export Financing Agency (LPEI) gave the facility is expected to financing, guarantees, and insurance in order to export in order to realize the national large-scale exports and the impact on economic development in Indonesia. The enactment of Act No. 2 of 2009 on LPEI mandates that the agency will eventually overcome various obstacles that are often faced by SME oriented export activities. Keywords: Role of Exports Financing Agency Against Small AndMedium Based on Law No. 2 Year 2009 About the OrganizationIndonesian Export Financing